Assessing the risk of SARS-CoV-2 transmission in international professional golf - Robinson, P. G.; Murray, A.; Close, G.; Kinane, D. F. (BMJ Open Sport & Exercise Medicine, 2021)
Objectives There is no published data on the incidence or risk of SARS-CoV-2 transmission when playing golf, a sport played outdoors where social distancing is possible. The purpose of this prospective study was to report incidence and transmission regarding SARS-CoV-2, of professional golfers competing on the PGA European Tour across 23 events in 11 countries.